1963
DOI: 10.1172/jci104720
|View full text |Cite
|
Sign up to set email alerts
|

The Pressor Effect of Tyramine in Man and Its Modification by Reserpine Pretreatment*

Abstract: Reserpine has been shown to cause depletion of catecholamines in various isolated tissues and in pharmacological preparations of intact animals (1)(2)(3)(4)(5). Several aspects of the alterations in body function associated with administration of reserpine to man have been reported: in two schizophrenics who had received reserpine, de la Lande and associates (6) showed that ephedrine infused into the brachial artery had no effect on forearm blood flow; Westfall and Watts (7) showed that in normal students ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1964
1964
1983
1983

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Further, the vasoconstriction observed during tyramine infusion suggested that the postganglionic sympathetic nerves contained norepinephrine. Both animal (20) and human studies (21,22) indicate that the hemodynamic effects of tyramine are due to its ability to release norepinephrine from sympathetic nerve endings.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the vasoconstriction observed during tyramine infusion suggested that the postganglionic sympathetic nerves contained norepinephrine. Both animal (20) and human studies (21,22) indicate that the hemodynamic effects of tyramine are due to its ability to release norepinephrine from sympathetic nerve endings.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported partial or complete inhibition of the Valsalva overshoot (1,2 ) and mild orthostatic hypotension (3) this has not been confirmed by other investigators (4-6). Investigations of the effects of reserpine on vasoconstrictor responses have produced variable results.…”
mentioning
confidence: 90%